Strategi public relation bank syariah di era digital - Fitriah, Destiana Mahmudatul (Maliki Interdisciplinary Journal, 2025)
This study examines the public relations strategy employed by Islamic banks to address communication challenges in the digital age. Advances in information technology have encouraged Islamic financial institutions to innovate in their information delivery and build a positive public image. Using descriptive qualitative methods, this study explores how Islamic banks utilize social media, websites, and other digital platforms to strengthen client relationships and increase public trust. The results indicate that implementing digital-based PR tactics significantly contributes to strengthening reputations and expanding the reach of Islamic product promotions. Furthermore, interactive communication and educational content also play a role in increasing Islamic financial literacy. Therefore, implementing flexible PR strategies in the digital age is key for Islamic banks in maintaining their image, attracting new customers, and maintaining customer loyalty.